Factors contributing to employees work stress in TNB Kluang / Adibah Ismail - Ismail, Adibah (Faculty of Business and Management, 2014)
Work stress was generating increasing concern among the public, media, employers and trade union. Workplace health and safety representatives in many countries are seeking solutions to the nature and causes of the problem as well as the legal requirements relating to its prevention and control. According to that, this paper aims to study the ‘Factors Contributing to Employees Work Stress in TNB Kluang’. The independent variables that involved in this study are workload, role conflict and interpersonal relationship at the workplace. For this project paper, this research focused on the employees that have been working at Tenaga Nasional Berhad, Kluan Johor. As 132 questionnaires were distributed to the employees and the data will be analyze by using the Statistical Package for Social Sciences (SPSS) version 2.0 programs. The variable data that will be used by the researcher is Frequency Distribution, Reliability Analysis, Multiple Regression and Correlations Analysis to answering the three of research objectives in this study. In the end of this paper, the researcher will be discussing about the result of this study and provide some recommendations for the future research.